Fundamental study of osteoclast chemotaxis toward chemoattractants expressed in periodontitis. (16th April 2013) - Niwa, T.; Mizukoshi, K.; Azuma, Y.; Kashimata, M.; Shibutani, T.
Abstract : Background and Objective: Periodontitis is a chronic inflammatory disease that leads to bone resorption by osteoclasts (OCs). Several factors contribute to the differentiation of OCs from hematopoietic precursors. Cellular chemotactic factors are expressed in periodontitis tissue, but the effects of these chemoattractants on OCs are not well understood. Here we examined the effects of chemoattractants produced in inflamed periodontal tissue on OC chemotaxis. Material and Methods: Rat bone‐marrow OCs were cultured in OC culture medium for 3 or 6 d. Using EZ‐TAXIScan™, the chemotactic response of these OCs to several chemoattractants [monocyte chemotactic protein‐1; macrophage inflammatory protein 1α; regulated on activation, normal T‐cell expressed and secreted; stromal cell‐derived factor‐1α; and complement activation product 5a (C5a)] was measured. In addition, we measured the effect of C5a‐specific inhibitors on chemotactic responses toward C5a. The recorded chemotactic responses were quantitatively analysed usingImage J software. Results: Chemoattractants associated with periodontal disease significantly increased the chemotactic activity of differentiated rat OCs in a concentration‐dependent manner, with C5a inducing the highest chemotactic activity of OCs cultured for 3 or 6 d. The C5a‐specific inhibitor significantly inhibited chemotaxis toward C5a in a concentration‐dependent manner. Conclusion: We suggest that C5a plays an important role in pathologic bone resorption in periodontal disease by stimulating the chemotaxis of OCs. Therefore, C5a is a potential target for the treatment of periodontal disease.